SIMULASI MODEL SWOT-AHP DALAM PENENTUAN PILIHAN ALTERNATIF STRATEGI PENGEMBANGAN PERGURUAN TINGGI VOKASI D3 - Hermada Dekiawan; Hasan Subagyo (Universitas Brawijaya, 2018)
This study aims to apply the concept of SWOT combined with Analytic Hierarcy Process (AHP) in the determination of alternative policy or development strategies. The data used in this study are hypothetical data simulated in the SWOT-AHP model. Given that this study is a model simulation, there are several assumptions used before the data is simulated into the SWOT-AHP model. There are three development alternatives assumed in this study: (1) college diversification and differentiation, (2) development of university into polytechnic or D4 or S1, and (3) development of supporting business unit of university. The three alternatives are analyzed by SWOT-AHP approach in order to determine appropriate development alternatives through 32 questions. The result of the study show that the SWOT-AHP model can be used in the determination of alternative college development. In the implementation, the number of respondents, as well as the parties involved need to be adjusted in order to provide optimal result.